An Exploratory Study Proposal On The Impact Of Csr Dısclosures Among Malaysıan Indıvıdual Investors - Fum Qi Teng; Low Mei Peng (Universitas Internasional Batam, 2021)
This paper aims to propose an exploratory study to understand individual investor’s investing decisions in relation to the impact of CSR disclosures of companies in Malaysia. More precisely, this paper uses an exploratory qualitative approach to develop a ground understanding of the individual investors’ evaluation of their perceptions towards a company’s CSR position during the investment decision-making process, particularly in the Malaysian context. Semi-structured interviews will be conducted using open-ended interview questions as the instrument for the richer and descriptive data collection on in-depth individuals’ experiences. Furthermore, this study is valuable in revealing specific issues and interests related to CSR disclosures and investment decisions that had not been previously identified in the existing research